Resource Allocation for Dual-Hop OFDM Systems with Multiple Decode-and-Forward Relays - Yicheng Lin; Wenbo Wang; Bin Fan; Lin Huang; Kan Zheng (2009 IEEE 70th Vehicular Technology Conference Fall, 2009)
In this paper, we consider the optimal resource allocation problem for dual-hop systems with a source-destination pair and multiple decode-and-forward (DF) relays. Orthogonal frequency division multiplexing (OFDM) is adopted in both hops. To maximize the system capacity, we formulate a mixed binary integer programming problem to optimally allocate the subchannels and transmit power for both the source and the relay nodes. Because of the prohibitive complexity, a greedy heuristic algorithm is proposed to decompose the original problem into solvable subproblems. Simulation results demonstrate that the proposed algorithm has a near-optimal performance.